PENGARUH SIKAP DAN MOTIF PEMBELIAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA SUPERMARKET DUTALIA KUPANG - Videlis Ndaumanu; Gaudensius Tisu (Parsimonia - Jurnal Ekonomi dan Bisnis, 2017)
Kupang Dutalia Supermarket is the biggest retail in the Kupang City, which is frequently visited by many consumers. They come to this supermarket to meet their daily needs. Hence, sale volume is fluctuated. The results of descriptive statistical analysis indicated that consumer’s attitude index was 79,86%, buying motive was 77,14% and buying decision was 80,00%; all were categorized as in high level. The results of multiple linear regression were as follow: Y= 5,383+0,413X1+0,065X2+e. The results of test showed that the consumer’s attitude had a positive and significant effect on buying decision, while the buying motive had a positive but insignificant effect on the buying decision. The determination coefficient (R2) indicated that the independent variables contributed 20,6% to buying decision, while the rest of 79,4% was contributed by other variables excluded in this study. It is recommended that in raising buying decision, Kupang Dutalia Supermarket management pay more attention to products’ arrangement so that the consumers will be easy to find their needed products and to add some more entertaining facilities in order to push consumers to go for shopping.